2014
DOI: 10.1007/s00167-014-2889-5
|View full text |Cite
|
Sign up to set email alerts
|

Deep-dished highly congruent tibial insert in CR-TKA does not prevent patellar tendon angle increase and patellar anterior translation

Abstract: Case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
(66 reference statements)
0
12
0
Order By: Relevance
“…Although there are many advantages of PCL retention in TKA, such as physiological femoral rollback, good range of motion, and few patellar complications [1, 2, 6, 7, 10], the post‐surgical function of the PCL may not be ideal because of damage during surgery or rupture during the follow‐up period. Hence, post‐cam mechanisms are often used to substitute for the PCL [9, 18, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many advantages of PCL retention in TKA, such as physiological femoral rollback, good range of motion, and few patellar complications [1, 2, 6, 7, 10], the post‐surgical function of the PCL may not be ideal because of damage during surgery or rupture during the follow‐up period. Hence, post‐cam mechanisms are often used to substitute for the PCL [9, 18, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers investigated patellar tracking in vitro, using cadaver knees or numeric simulations, because of difficulties in recording dynamic measurements in patients [5,20,27,33,42]. Some clinicians studied patellar position in vivo, using static radiographic images, and correlated it with clinical and functional outcomes [3,7,30,41,48,55]. Very few studies, however, compared patellar position in relation to tibiofemoral kinematics before and after knee arthroplasty in vivo [10].…”
Section: Resultsmentioning
confidence: 99%
“…Very few studies, however, compared patellar position in relation to tibiofemoral kinematics before and after knee arthroplasty in vivo [10]. While the patellar tilt and congruence are commonly measured at 20° to 45° of flexion to assess engagement within the trochlear groove [34,40], the patellar tendon angle (PTA) and height are often measured at 90° of flexion to assess extensor mechanism lever arm and its impact on tibiofemoral kinematics [3,6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, training (Kubo et al, 2001;Reeves et al, 2003;Arampatzis et al, 2007;Kongsgaard et al, 2007) and disuse (de Boer et al, 2007) studies have shown changes in tendon morphological, mechanical, and material properties. It follows that changes in tendon mechanical loading observed in TKA patients (Stagni et al, 2010;Akkawi et al, 2014) may require such adaptations (Galloway et al, 2013) to prevent injury and/or to maintain functional capacity. However, morphological and material adjustments following TKA and/or exercise training are currently undocumented in these patients.…”
mentioning
confidence: 99%